x-5-(-2)+2x=7

Simple and best practice solution for x-5-(-2)+2x=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-5-(-2)+2x=7 equation:


Simplifying
x + -5 + -1(-2) + 2x = 7

Multiply -1 * -2
x + -5 + 2 + 2x = 7

Reorder the terms:
-5 + 2 + x + 2x = 7

Combine like terms: -5 + 2 = -3
-3 + x + 2x = 7

Combine like terms: x + 2x = 3x
-3 + 3x = 7

Solving
-3 + 3x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 3x = 7 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = 7 + 3
3x = 7 + 3

Combine like terms: 7 + 3 = 10
3x = 10

Divide each side by '3'.
x = 3.333333333

Simplifying
x = 3.333333333

See similar equations:

| Q-2.4=1.8 | | 3b=6v+3b | | 10y+18=-3(5y-7)+5y | | 4n^2-4n-6=0 | | K-56=107 | | y+5=-7x-21 | | x^2-y^2-3x+3= | | x+x+2+x+2=75 | | (x^2-2x-1)+(2a^2+2a+3)= | | 3g+2(-5+2g)=1-g | | 2(a+1)+4a=-10 | | x^2(x^2+x+1)=0 | | 8(p+1)-6p=24 | | 5(x+4)=3x+14 | | 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 | | x/7=5 | | 12x+7y=-35 | | x^3+125y^3= | | k+3(3)=45 | | 500-3x=275 | | 6(-1-d)=-42 | | n-10=.3n-7-.3n | | (3u+7)(6-u)=0 | | 2-11-19= | | b^4-32b^2+256= | | 70uv-91uw= | | 2x-19= | | 1/3(6z+10)= | | 7b^2+43b+40=0 | | 7(n+3)=6(n-3) | | 13t+8=4t+73 |

Equations solver categories